Euthanasia in Ecuador and Latin America: A Comparative Study using Neutrosophic Logic and Multivariate Analysis - Manuel Richard Naranjo Rodríguez; Sandra Dayanara Correa Solis; Alexander Joshua Bajaña Jiménez (Neutrosophic Sets and Systems)
This study aims to analyze the legal, social, and cultural factors that influence the legalization of euthanasia in Ecuador, using a comparative approach with other Latin American countries. The central problem lies in the lack of a comprehensive understanding of how variables such as the degree of secularism, access to palliative care, population religiosity, and ethical and professional perceptions relate to each other in the legislative debate on euthanasia. To this end, a database with 300 records was constructed, integrating quantitative, qualitative, and neutrosophic variables, which allow for the capture of both structural data and ambiguous assessments of morality and professional opinion. The methodology applied is based on Principal Component Analysis (PCA), which allows for the identification of latent axes of variability in the phenomenon, along with a neutrosophic approach that accounts for the uncertainty inherent in ethical judgments. The results show that the first principal components are strongly influenced by factors such as HDI, positive moral appraisal, and religiosity, revealing clusters of records with similar normative and cultural profiles. It is concluded that euthanasia is a multidimensional phenomenon, whose understanding requires the use of methods that capture both latent structures and ethical ambiguity, with PCA and Neutrosophic being key complementary tools in this analysis.